Implementation of School Community Program and Teacher’s Participation in School Events in Marawi City Division (American Journal of Arts and Human Science, 2025)
The strength of a school community is essential for a successful educational institution, particularly in the Marawi City Division, where sociocultural and educational challenges exist. This study examined the implementation of the school community program and the extent of public elementary school teachers’ participation in various school events. A descriptive survey approach was used, with 250 teachers participating, and the data were analyzed using descriptive and inferential statistics. Results showed a high level of program implementation, with religious activities being the most implemented and economic activities the least. Teachers’ participation in school events was also generally high, with the greatest involvement during Ramadan and the lowest in cultural dance activities. Significant differences in participation were observed based on age, sex, and ethnicity. The study proposed a school development plan to enhance the program’s implementation, particularly in economic activities and outreach programs. It recommended a comprehensive development strategy to address diverse community needs, strengthen external collaborations, and promote inclusivity. Overall, while the school community program and teachers’ participation in Marawi City Division are strong, further improvements are necessary to create a more inclusive and impactful school-community connection.